Cahokia jazz : a novel - Spufford, Francis, 1964- (Scribner, 2024)
"Like Golden Hill, Cahokia Jazz inhabits a different version of America, and like Golden Hill it has a propulsive and brilliantly twisty plot set within a fully imagined world. Only this world is full of fog, cigarette smoke, dubious motives, danger, and dark deeds. And in the main character of Joe Barrow, we have a hero of truly heroic proportions, and a troubled soul to fall in love with. One snowy night at the end of winter, Barrow and his partner find a body on the roof of a skyscraper. Down below, streetcar bells ring, factory whistles blow, Americans drink in speakeasies and dance to the tempo of modern times. But this is Cahokia, the ancient indigenous city beside the Mississippi living on as a teeming industrial metropolis containing every race and creed. Among them, peace holds. Just about. But the corpse on the roof will spark a week of drama in which this altered world will spill its secrets and be brought, against a soundtrack of wailing clarinets, either to destruction or to rebirth"--